Efektivitas Terapi Slow Deep Breathing Terhadap Ibu Hamil Dengan Emesis Gravidarum Di BPM Puspitarini, A.Md.Keb Kecamatan Glenmore - Febrika Devi Nanda (Pusat Riset dan Inovasi Nasional, 2022)
Nausea, vomiting is a normal symptom experienced by most pregnant women. This condition is common in early pregnancy, especially in the first week to the third month of pregnancy. Nausea and vomiting in pregnant women is often called morning sickness or can be called emesis gravidarum, but there are some pregnant women who experience nausea and vomiting anytime and anywhere, whether in the morning, afternoon or evening. This research uses a quasi-experimental research design with a One Group Pretest-Posttest Design research design. This research was conducted to determine the effectiveness of slow deep breathing therapy for pregnant women with emesis gravidarum. From the research results, the results showed that before slow deep breathing therapy was carried out, there was a mild level of nausea and vomiting, namely 16 respondents (53.30%). Meanwhile, those who had moderate levels of nausea and vomiting were 14 respondents (46.70%). Then, after being given slow deep breathing therapy, the majority of respondents had mild nausea and vomiting, namely 30 (100%). The pre-test and post-test show a significant relationship with the criteria for nausea and vomiting in pregnant women with a p value = 0 <0.05 N = 30, so it can be concluded that there is a significant effect of effectiveness between slow deep breathing therapy on nausea and vomiting in pregnant women in BPM. Puspitarini, A.Md. Keb, Glenmore District.